IDEOLOGISASI DALAM PENEGAKAN KHILAFAT AHMADIYAH: Studi Kasus Jemaat Ahmadiyah di Kampung Gondrong Tangerang Banten - Kunu, Arifuddin (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2016)
By applying the nizam khilafat ahmadiyah (khilafah ‘ala minhaji an-nubuwah), Ahmadiyah continues to grow and shows rapid development. Khilafat in Ahmadiyya also allows the congregation to unite under the orders of a Caliph. In practice, khilafat in Ahmadiyah involves the concept of doctrine and ideology that has been constructed both socially, culturally and spiritually. This study aims to determine the role of organizational doctrine and ideology in perpetuating the khilafat system for Ahmadiyah followers. The study was conducted in Kenanga Village, Cipondoh Subdistrict, Tangerang City, Banten. This research is qualitative by applying methods of observation, interviews and literature research. The results showed that ideology and doctrine delivered in a structured and systematic manner had perpetuated the khilafah in Ahmadiyya while at the same time fostering the loyalty of all members of the congregation. To cite this article (7th APA Style): Kunu, A. (2016). Ideologisasi dalam Penegakan Khilafat Ahmadiyah: Studi Kasus Jemaat Ahmadiyah di Kampung Gondrong Tangerang Banten [Ideologization in Building the Ahmadiyya Empire]. Journal Communication Spectrum, 6(1), 15-27